2016
DOI: 10.1186/s40348-016-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

The puzzle of immune phenotypes of childhood asthma

Abstract: Asthma represents the most common chronic childhood disease worldwide. Whereas preschool children present with wheezing triggered by different factors (multitrigger and viral wheeze), clinical asthma manifestation in school children has previously been classified as allergic and non-allergic asthma. For both, the underlying immunological mechanisms are not yet understood in depth in children. Treatment is still prescribed regardless of underlying mechanisms, and children are not always treated successfully. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
0
13
0
2
Order By: Relevance
“…However, clinical practice and also molecular studies still divide children into two main phenotypes, namely allergic and nonallergic asthma . Attempts were made to disentangle distinct underlying pathophysiological mechanisms, but were hampered by the complex nature of the disease . While singular targets were identified, one could not consistently pinpoint a reliable pattern of relevant pathways critical for asthma phenotype differentiation and in the long‐term potentially patient‐tailored treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical practice and also molecular studies still divide children into two main phenotypes, namely allergic and nonallergic asthma . Attempts were made to disentangle distinct underlying pathophysiological mechanisms, but were hampered by the complex nature of the disease . While singular targets were identified, one could not consistently pinpoint a reliable pattern of relevant pathways critical for asthma phenotype differentiation and in the long‐term potentially patient‐tailored treatment of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…As mice from the positive control group were severely sicker than mice from the AIT-groups it is clear that the number of FoxP3 + cells alone does not provide information about the immunological tolerance of an organism. Also studies in humans observed increased numbers of Tregs in asthmatic patients (Landgraf-Rauf et al, 2016). One could speculate whether rather the quality and not the quantity of regulatory T cells is decisive for tolerance induction.…”
Section: Discussionmentioning
confidence: 97%
“…Результаты исследования свидетельствуют, что у детей с персистирующим фенотипом бронхиальной обструкции вне зависимости от пола и возраста статистически значимо повышаются концентрации как провоспалительных (IL-6, IL-8), так и противовоспалительных цитокинов (IL-4). Клинические данные свидетельствуют о значимости Th2цитокина IL-4 в поддержании воспаления и формировании бронхиальной гиперреактивности [6][7][8][9][10]. Вместе с тем в ряде исследований показано, что повышение уровней провоспалительных цитокинов является особенностью созревания иммунной системы в раннем возрасте; появляется все больше доказательств того, что экспрессия Th1-цитокинов (IL-1β, IL-8) имеет существенное значение в патогенезе рецидивирующего СБО у детей [10,11].…”
Section: Discussionunclassified